Frontiers in premature beats research: a bibliometric analysis - Wu, Dan; Xia, Xiaojing (Frontiers in Cardiovascular Medicine, 2024)
Background This study aimed to assess the scientific results and activities of premature beats research from a global perspective. Methods Publications related to premature beats published between 2003 and 2024 were identified and selected from the Web of Science core collection. VOSviewer was used to conduct co-authorship, co-citation, and co-occurrence analyses of the authors, organizations, countries/regions, references, sources, cited authors, and keywords. Results In total, 5,283 publications on the topic of premature beats were identified from the Web of Science core collection. The number of publications on this topic has steadily grown since 2003. Fred Morady, Frank Bogun and Krit Jongnarangsin were the top three researchers with the strongest total link strengths. The University of Washington, Johns Hopkins University, and the University of Minnesota are the top three organizations with the strongest total link strengths. The United States has made the greatest contributions to the field of premature beats. Haïssaguerre, M et al.'s publication in The New England Journal of Medicine in 1998 entitled “Spontaneous initiation of atrial fibrillation by ectopic beats originating in the pulmonary veins” is the most cited reference. The most cited references come from the journal named Circulation. Haïssaguerre, M has the highest number of citations. The keywords for all current publications can be divided into four categories: “mortality rate,” “risk and prevention,” “mechanism,” and “classification and treatment.” Conclusions This bibliometric study provides insights into the current status and research trends in premature beats over more than 20 years. Future research will focus on an in-depth exploration of the nature of premature beats, especially ventricular premature beats, mastering the development law of premature beats, and optimizing existing detection methods.